The Effect of Elderly Exercise on Blood Pressure Among Older Adults with Hypertension in Lumban Pea Village, Balige District, Toba Regency, 2026 - Erita Saragih; Munarni Simatupang (International Journal Of Health Science, 2026)
The physiological aging process triggers a decline in vascular function, which impacts the high escalation of hypertension cases in the elderly population. This study aims to analyze the empirical effect of elderly gymnastics on reducing blood pressure among elderly hypertensive patients in Lumban Pea Village, Balige District, Toba Regency in 2026. This type of research was quantitative with a pre-experimental design using a one-group pretest-posttest design without a control group. The sample in this study consisted of 31 respondents selected using a purposive sampling technique from a total population of 35 hypertensive elderly. The elderly gymnastics intervention was conducted twice a week for three weeks with a duration of 30 minutes per session. Blood pressure measurements were taken using a calibrated digital sphygmomanometer 30 minutes before and after the entire intervention series. The results of the univariate analysis showed a decrease in mean systolic blood pressure from 150.00 mmHg to 140.48 mmHg, and diastolic pressure from 94.48 mmHg to 90.48 mmHg. The Shapiro-Wilk normality test indicated that the data were normally distributed ( ). Based on the bivariate Paired Sample T-Test, a p-value of 0.001 was obtained for systolic pressure and 0.003 for diastolic pressure ( ). In conclusion, elderly gymnastics has a significant effect on lowering systolic and diastolic blood pressure through the mechanism of blood vessel vasodilation and decreased sympathetic nerve activity.